Pengaruh Program Tahfizh Al-Qur’an terhadap Pembentukan Karakter Santri di Pondok Pesantren Al-Aziziyah Kapek - Muhammad Ilham Hadinugraha (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to comprehensively analyze the effect of the Al-Qur'an tahfizh program on the character formation of students at Pondok Pesantren Al-Aziziyah Kapek. A quantitative approach with a quasi-experimental design was employed, involving experimental and control groups. The sample consisted of 30 students (15 experimental, 15 control). A questionnaire was administered as the instrument during the pretest and posttest. Data were analyzed using the Independent Samples t-test after normality and homogeneity tests. The results showed a significance value of 0.006 (<0.05), indicating a significant effect of the tahfizh program on student character. The experimental group demonstrated higher character improvement compared to the control group. Systematic and sustained Qur'an memorization activities internalize spiritual and moral values such as discipline, responsibility, patience, and honesty. The implication is that the tahfizh program can serve as an effective strategy for character education in Islamic boarding schools. Optimizing the program through strengthening learning methods, continuous mentoring, and educator role modeling is essential to foster a generation with noble character and Islamic personality